1994
DOI: 10.1002/polb.1994.090320403
|View full text |Cite
|
Sign up to set email alerts
|

Miscibility behavior of di(ethyl‐2 hexyl) phthalate in binary and ternary chlorinated polymer blends

Abstract: The miscibility behavior of ternary blends made by the addition of di(ethyl‐2 hexyl) phthalate (DOP) to a mixture of chlorinated polymers was investigated by differential scanning calorimetry. Two chlorinated polymer mixtures were selected: polyvinyl chloride (PVC) with a chlorinated polyethylene containing 48 wt% Cl (CPE48), and PVC with a chlorinated PVC containing 67 wt% Cl (CPVC67). Each binary DOP/chlorinated polymer pair is miscible whereas PVC/CPE48 and PVC/CPVC67 blends are immiscible. DOP/CPE48/PVC an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…In both models, the conditions under which spherical micelles can form were investigated and expressions of the critical micelle concentration, 0cmc8pherical> were derived. Leibler,72 for example, gives (5) with Zha the degree of polymerization of the homopolymer A and Zcb the degree of polymerization of the B block of the copolymer. The predictions of 0cmc were recently extended by Shull et al17 to the cases of cylindrical and lamellar micelles.…”
Section: Introductionmentioning
confidence: 99%
“…In both models, the conditions under which spherical micelles can form were investigated and expressions of the critical micelle concentration, 0cmc8pherical> were derived. Leibler,72 for example, gives (5) with Zha the degree of polymerization of the homopolymer A and Zcb the degree of polymerization of the B block of the copolymer. The predictions of 0cmc were recently extended by Shull et al17 to the cases of cylindrical and lamellar micelles.…”
Section: Introductionmentioning
confidence: 99%
“…The polymer matrix is poly͑methyl methacrylate͒ ͑PMMA͒. The plasticizer is di͑ethyl-2 hexyl͒ phthalate ͑DOP͒ 7,8 . The solution of MNA and PMMA in methyl isobutyl ketone ͑MIBK͒ was made.…”
Section: ͓S0003-6951͑96͒00346-4͔mentioning
confidence: 99%
“…20 The miscibility behavior of DOP/CPE48/PVC and DOP/PVC/ CPVC67 ternary blends was influenced by the di-isooctyl phthalate (DOP) concentrations. 21 So far, no study has been reported on the use of DOP as plasticizing agent for PVC/a-MSAN blend system. This work attempts to investigate the compatibility between PVC and a-MSAN copolymers via dynamic mechanical analysis (DMA) and scanning electron microscopy (SEM) methods.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Paul and coworkers have found that the addition of DMP first lowers the cloud point for the PMMA/SAN blend system, but further addition causes the cloud point to increase 20. The miscibility behavior of DOP/CPE48/PVC and DOP/PVC/CPVC67 ternary blends was influenced by the di‐isooctyl phthalate (DOP) concentrations 21. So far, no study has been reported on the use of DOP as plasticizing agent for PVC/α‐MSAN blend system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation